IMPLIKASI INTEGRASI PENGEMBANGAN SOFTSKILL, DAN AUGMENTED REALITY PADA PENDIDIKAN DASAR DI ERA DIGITAL - Rozi, Fahrur; Fauzi, KMS. M. Amin (Universitas Negeri Medan, 2024)
Improved Softskill Development and Augmented Reality In addition to focusing on mastery of academic material, basic education increasingly emphasizes the development of soft skills or soft skills that are essential for success in this digital era. Universitas Negeri Medan (UNIMED) as one of the LPTK that produces teachers since 2011 has set a strategy towards 2025 by launching the development of its role in producing quality teachers. One of the directions developed is to make UNIMED as